Income Tax Policy in Europe between Two Crises: From the Great Recession to the COVID-19 Pandemic - Michal Myck; Kajetan Trzciński (Institute of Labor Economics (IZA), 2022)
We examine the revenue and redistributive effects of tax policy reforms in twelve European countries over the decade between the financial crisis and the outbreak of the COVID-19 pandemic, setting them against the implications of a hypothetical system reflecting the extent of fiscal drag resulting from nominal wage increases. We show that the combination of wage growth and progressivity of the tax system determined the fiscal leeway which governments could use to reduce income inequality. Despite significantly faster wage growth in the examined post-communist countries of Central and Eastern Europe, their much lower degree of progressivity implied limited additional scope for fiscal changes. While decisions taken in most of the examined countries in the CEE region led to increases in tax progressivity, their income tax systems continue to be far less redistributive in comparison with such countries as Ireland, the Netherlands, or Portugal. This not only has direct implications for income inequality but also translates into limitations of automatic fiscal drag effects on government revenues, which could offer additional resources, in particular at a time of high inflation.
Keywords: H24; D31; 330; income tax; tax reforms; fiscal drag